Leading in a culture of change - Fullan, Michael (San Francisco, CA Jossey-Bass, 2001)
"Business, nonprofit, and public sector leaders are facing new and daunting challenges - rapid-paced developments in technology, sudden shifts in the marketplace, and crisis and contention in the public arena - if they are to survive in this chaotic environment, leaders must develop the skills they need to lead effectively no matter how fast the world around them is changing." "Leading in a Culture of Change offers new and seasoned leaders' insights into the dynamics of change and presents a unique and imaginative approach for navigating the intricacies of the change process. Author Michael Fullan shows how leaders in all types of organizations can accomplish their goals and become exceptional leaders. He draws on the most current ideas and theories on the topic of effective leadership, incorporates case examples of large scale transformation, and reveals a remarkable convergence of powerful themes or, as he calls them, the five core competencies."--Jacket.
A remarkable convergence -- Moral purpose -- Understanding change -- Relationships, relationships, relationships -- Knowledge building -- Coherence making -- The hare and the tortoise.
Includes bibliographical references (pages 139-144) and index.
Keywords: Educational leadership; School management and organization; Educational change